Upaya Meningkatkan Hasil Belajar Seni Tari Melalui Metode Kooperatif Learning Di Fase E SMA Negeri 10 Padang - Putri Bunga Gettalia; Susmiarti Susmiarti (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
The purpose of this study was to improve the learning outcomes of dance for Padang 10 Public High School students using the Jigsaw Type learning method. The type of research is classroom action research. The research instrument was a test given at the end of each cycle. Primary data and secondary data are used in this research material. Data collection techniques are carried out through observation, tests, and documentation. Data analysis techniques use qualitative and quantitative analysis. The results of the study prove that student performance and learning outcomes increase with the application of cooperative learning methods in puzzle-type dance education at SMA Negeri 10 Padang. It can be seen that in the 2nd cycle, the percentage of classical perfection of students' learning outcomes in the cognitive domain rose to 92% with very good score criteria, while in the 1st cycle, the percentage of students' learning classical perfection with low results was only 72%. The learning outcomes of students' abilities (psychomotor) were also very good as seen from the classical percentage of student learning outcomes in cycle I, namely 56% in cycle 2, rising to 88% with very good criteria. so the application of learning using the Jigsaw Type cooperative learning method can increase student performance and learning outcomes.